Optimization of Tillage Operation Parameters to Enhance Straw Incorporation in Rice-Wheat Rotation Field - Sagni B. Miressa; Qishuo Ding; Yinian Li; Edwin O. Amisi (Agriculture)
In the rice-wheat system, using straw for soil incorporation provides better soil health and improves agricultural production. The experiment was performed in Babaiqiao town, Jiangsu Province, China’s Luhe District, Nanjing City, in June 2024 using a Shichao TG-500 tractor equipped with a Qingxuan 1GKN-180 rotary cultivator. The impacts of the three tillage practices, deep rotary tiller with straw (DRTS), shallow rotary tiller with straw (SRTS), and no-tillage with straw return (NTSR), on the level of soil disturbance were observed in the single-factor and two-factor interaction experiments. Based on the profilometry analysis, it was observed that DRTS had the highest value of soil disturbance while SRTS had a moderate disturbance value and NTSR minimized disturbance. The effects of working depths, forward speed, and rotation speed on the straw return rate have been evaluated by further investigations. The results showed that enhancing straw return rates was significantly impacted by changing the tilling depths and the rotation speeds, especially when using deeper tillage and moderate to high rotary speeds. The investigation found that the forward speed, blade rotation speed, and tillage depth explained the overall rates of straw return, soil breaking, and soil flatness. In the research, the response surface design employed was the Box–Behnken Design (BBD). The optimal operating parameters were 14.23 cm of plowing depth, 297.6 rpm for the rotary blades, and 3.23 km/h for forward speed. Achieved were the following parameters: 94.766% soil breakage rate, 84.97% straw return rates, and 16.36 mm soil flatness. The findings demonstrate the potential to implement strategies through operational parameters to significantly enhance agricultural practices.